Emphysematous osteomyelitis with acute promyelocytic leukemia: a rare case report - Kumar, B. Vijay; Rao, G. Vamshi Nandan; Veena, M. (International Journal of Research in Medical Sciences, 2025)
Emphysematous osteomyelitis represents an infrequent clinical entity. The confluence of acute promyelocytic leukemia (APML), immunosuppression, and an elevated susceptibility to opportunistic infections—exacerbated by bacteraemia-may precipitate the pathogenesis of this gas-forming osteomyelitis process. A 63-year elder male presented to our hospital with consistent fever and chills from past one month. Hematological evaluation revealed pancytopenia. Subsequent bone marrow aspiration and flow cytometry confirmed a diagnosis of acute myeloid leukemia (AML), further substantiated by reverse transcriptase-PCR demonstrating a PML/RARA bcr-3 fusion transcript, confirming the diagnosis of acute promyelocytic leukemia (APML). The patient received a contemporary chemotherapy that included all-trans retinoic acid (ATRA) and arsenic trioxide (ATO), leading to a notable enhancement in the results. However, during treatment, he developed bacteraemia with Klebsiella pneumoniae, confirmed via blood and urine cultures. A high-resolution computed tomography (CT) scan unveiled the pathognomonic presence of intraosseous gas, confirming emphysematous osteomyelitis. Selected intravenous antibiotic therapy yielded in marked clinical amelioration, thus obviating the requirement for surgical debridement. This case underscores the imperative role of advanced imaging modalities in detecting rare infectious sequelae and demonstrates that, with prompt recognition and appropriate antimicrobial intervention, conservative management can yield favorable outcomes even in severely immunosuppressed hosts.